Synthesis, antibacterial evaluation, and safety assessment of CuS NPs against Pectobacterium carotovorum subsp. carotovorum. Issue 2 (15th November 2021) - Yan, Weiyao; Fu, Xuan; Gao, Yuan; Shi, Liyin; Liu, Qi; Yang, Wenchao; Feng, Jianguo
Abstract: BACKGROUND: Copper agents have been widely used in crop protection because of their unique mechanism against resistant pathogenic bacteria; however, their application brings environmental pollution and biosafety problems. Therefore, environmentally friendly copper agents have attracted attention. In this study, copper sulfide nanoparticles (CuS NPs) were prepared, characterized, analyzed for antibacterial activity and safety. RESULTS: Characterization results showed that the prepared pure CuS NPs have flake nanostructures, hexagonal crystal system, and size range from 40 to 60 nm. These CuS NPs exerted excellent antibacterial effects [median effective concentration (EC50 ) = 17 mg L −1 ] against Pectobacterium carotovorum subsp. carotovorum ( Pcc ) in vitro and can effectively delay and reduce bacterial infection in vivo . Antibacterial mechanism analysis revealed that CuS NPs can increase the levels of reactive oxygen species (ROS) and lipid peroxidation and destroy the structure of bacterial cells as observed through scanning electron microscopy (SEM) and Fourier‐transform infrared (FTIR) spectroscopy. These NPs can also inhibit the motility of Pcc . At 7 and 14 days, the 50% lethal concentrations (LC50 ) of CuS NPs against earthworms were 1136 and 783 mg kg −1, respectively, indicating their low acute toxicity to earthworms and environmental friendliness. Furthermore, the cells (L02) treated by CuS NPs showed relatively high cell viability (> 96%) and low apoptosis rate (only 5.2%), proving that CuS NPs had low cytotoxicity. CONCLUSION: Compared with commercial dicopper chloride trihydroxide (Cu2 (OH)3 Cl), CuS NPs could be used as a highly effective, lowly toxic, and environmentally friendly antibacterial agent. © 2021 Society of Chemical Industry. Abstract : The copper sulfide nanoparticles (CuS NPs) were prepared through simple coprecipitation, characterized through scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Prepared CuS NPs exhibit antibacterial activities against Pectobacterium carotovorum subsp. carotovorum ( Pcc ), protective ability to potatoes, and safety to L02 cells and earthworm.